Sanksi Pidana terhadap Penumpang yang Membawa Barang Berbahaya dalam Penerbangan - Ibnu Maruf; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2021)
Aviation is the transportation that is chosen by many people to support their mobility and travel efficiency. In order to maintain comfort for users of aviation transportation, the operation of flights and their supervision is regulated directly by the national transportation unit system in an integrated and systematic manner. This study aims to examine the legal arrangements for passengers who carry dangerous goods on flights and reveal criminal sanctions against passengers who carry dangerous goods on flights. This study was designed using normative legal research, with a legislative and conceptual approach. The data used are sourced from primary, secondary and tertiary legal materials obtained through reading activities. Then analyzed using literature study. The results of the study reveal that legal arrangements regarding passengers carrying dangerous goods on flights are regulated in detail and firmly in Law No. 1 of 2009 concerning Aviation, Government Regulation No. 3 of 2001 concerning security and safety in flights and the sanctions given to perpetrators who carry dangerous goods are: imprisonment for 2 years and a fine of Rp. 500,000,000